Necesidad de reformar el art. 556 del COOTAD en lo referente a la plusvalía, ya que es causal de desigualdad en la población del Ecuador - Ávila Angulo, Ruddy Darío (2015)
It is important to understand that laws and regulations are set to regulate life in society, indicate what is good and acceptable, what are our obligations and rights. But it should be noted that these laws must be commensurate with the real needs of all citizens; ie ensuring that the compliance therewith does not conflict with the content under the good life of the Constitution. It is for these indications how to amend Article 556 of the Code of Territorial Organization, Autonomy and Decentralization, COOTAD as it is seen that the current recovery ratio serves to undermine something these inalienable rights is analyzed that as citizens of this country we have. It is for all these reasons it is very important to recognize the rights you have and even be able to propose amendments to the regulations need. Since this legislation is applied according to the needs of each province / city needs to do a review for the collection of this tax is equitable manner throughout the area comprising the Ecuador? But doing an analysis of the inequalities that exist in the country; between regions, social classes etc